Heavy Metals Distribution in the Artisanal Gold Mining Area in Wonogiri - Mohammad - Nurcholis; Dwi Fitri Yudiantoro; Darban - Haryanto; Abdurrachman - Mirzam (Faculty of Geography, Universitas Gadjah Mada, 2017)
Artisanal and small gold mining activity in Wonogiri Regency has long been done with problems on environmental quality. This study was aimed to analyze the levels and spatial distribution of heavy metals in the mining area. Survey of mining and amalgamation sites, sampling the soil and tailings had been conducted. There were 66 samples of soil and tailing were collected, analysis of heavy Fe, Mn, Pb, Hg, As and Co, using X-ray fluorescence (XRF). Normal distribution test of data was conducted using the Kolmogorov-Smirnov and Shapiro Wilk. The spatial distribution of heavy metals was described using Krigging method. Contents of most heavy metals in the area studied were high, except for Co. According to the distribution pattern of heavy metals indicated that the contamination caused by the mining.